Laboratory methods in molecular biology / Nor' Aishah Hasan … [et al.] - Hasan, Nor' Aishah; Mohd Zan, Mohd Syahril; Ahmad, Noorlis; Hasbullah, Nur Intan
Molecular Biology Laboratory is designed for laboratory work mid-level biology courses. Seven experiments are included in this manual which provide student with the relevant techniques and skills in molecular biology. Preparation of solution is provided in earlier experiment for students to prepare and hands on with the solution involved in molecular biology experiment. This manual contains the cloning procedure which involves extraction of DNA, extraction of plasmid, restriction enzyme, transformation, PCR and sequencing. Molecular Biology Laboratory involved with many equipment and it is very important for the students to be familiar and understands the application of the machine. In addition, this manual also includes post lab questions that will guide students and assist them in writing lab reports. We would like to acknowledge the people that direct and indirectly involved in writing up of this manual for their support, assistance and advice. We hope by using this manual, students will be ask to conduct related experiments wisely.